Gemcitabine and cisplatin-based combination chemotherapy in advanced hepatocellular carcinoma: An Indian experience - Shripad B Pande; D C Doval; K Pavithran; J B Sharma; Rashmi Shirali; A Jena (Indian Journal of Medical and Paediatric Oncology)
Background: Gemcitabine, an anti-metabolite, has some activity in hepatocellular carcinoma (HCC) in terms of responses and median survival. Aims: To analyze our experience with the use of gemcitabine in combination with cisplatin in HCC with respect to response, toxicity and survival. Materials and Methods: We studied the records of patients of HCC treated from January 2000 to December 2005 with gemcitabine and cisplatin, and found 24 of them to be evaluable for response, toxicity and survival. Results: Of 24 patients receiving three or more cycles of chemotherapy, six (25%) had a partial response and an additional 12 (50%) had stable disease. The median overall survival (OS) was 7.5 months (95% confidence interval, 4.5-10.5 months) and 1-year survival was 18%. Grade 3 and 4 anemia, thrombocytopenia and neutropenia were observed in, respectively, 17, 17 and 33% patients. The most frequent non-hematologic toxicities were nausea and vomiting and peripheral neuropathy. Conclusion: We report a partial response rate of 25% with stable disease in an additional 50% to three or more cycles of chemotherapy with gemcitabine and cisplatin, with a median OS of 7.5 months (95% confidence interval, 4.5-10.5) and acceptable toxicity profile from our single-center retrospective study of 24 patients of HCC. We trust that, in HCC, gemcitabine is a good drug to be the foundation to build the chemotherapeutic or targeted agents′ combinations on.